Adivina cuanto te quiero - McBratney, Sam.; Jeram, Anita (Barcelona : Kókinos, 1994)
During a bedtime game, every time Little Nutbrown Hare (Caramelo) demonstrates how much he loves his father, Big Nutbrown Hare (Papa Liebre) gently shows him that the love is returned even more.
Keywords: Hares -- Fiction; Fathers and sons -- Fiction; Bedtime -- Fiction; Spanish language materials; Love stories